Genomic and Phenotypic Diversity of Cultivated and Wild Tomatoes with Varying Levels of Heat Tolerance - Ayenan, Mathieu Anatole Tele; Danquah, Agyeman; Agre, Paterne A. (MDPI, 2021)
Assessment of genetic variability in heat-tolerant tomato germplasm is a pre-requisite to improve yield and fruit quality under heat stress. We assessed the population structure and diversity in a panel of three Solanum pimpinellifolium (wild tomatoes) and 42 S. lycopersicum (cultivated tomatoes) lines and accessions with varying heat tolerance levels. The DArTseq marker was used for the sequencing and 5270 informative single nucleotide polymorphism (SNP) markers were retained for the genomic analysis. The germplasm was evaluated under two heat stress environments for five yield and flower related traits. The phenotypic evaluation revealed moderate broad-sense heritabilities for fruit weight per plant and high broad-sense heritabilities for fruit weight, number of inflorescences per plant, and number of flowers per inflorescence. The hierarchical clustering based on identity by state dissimilarity matrix and UPGMA grouped the germplasm into three clusters. The cluster analysis based on heat-tolerance traits separated the germplasm collection into five clusters. The correlation between the phenotypic and genomic-based distance matrices was low (r = 0.2, p < 0.05). The joint phenotypic and genomic-based clustering grouped the germplasm collection into five clusters well defined for their response to heat stress ranging from highly sensitive to highly tolerant groups. The heat-sensitive and heat-tolerant clusters of S. lycopersicum lines were differentiated by a specific pattern of minor allele frequency distribution on chromosome 11. The joint phenotypic and genomic analysis revealed important diversity within the germplasm collection. This study provides the basis for efficient selection of parental lines to breed heat-tolerant varieties.
Keywords: genetic variability; heat tolerance; heritability; SNP markers; tomatoes; Peter Hanson; Isaac Kwadwo Asante; Eric Yirenkyi Danquah; Agric; University of Ghana